Effects of Dual Task Training Versus PNF Pattern on Balance and Cognition in Geriatric Population: Life Sciences-Physiotherapy - V, Rajalaxmi; Arthi, J; Kumar, G.Mohan; N, Muthukumaran; K, Balathandayutham; K, Saraswathi; Kavitha, E (International Journal of Life Science and Pharma Research, 2022)
The aim of this study is to examine the effects of Dual task training versus Proprioceptive Neuromuscular Facilitation (PNF) training on balance and cognition in geriatric population. There is growing evidence of the involvement of executive control in the maintenance of balance in older people. Balance is considered as one of the risk factors for fall especially in older adults. Proprioceptive Neuromuscular Facilitation training is one of the effective way to maintaining balance. PNF pattern exercise can activate joint sense by moving almost all joints of the body simultaneously. This is an experimental design with pre and post comparative study. This was conducted in the Physiotherapy Outpatient department in ACS Medical College and Hospital. The study duration was about 12 weeks. The subjects between the age group of 65 – 85 years of both sex those without orthopedic problems were included in this study. The subjects with severe dementia, severe cardiac problems, who had undergone recent surgery were excluded from the study. 50 Geriatric individuals were selected and divided into two groups in which Group AReceived Dual Task Training and Group B received PNF training for a period of 12 weeks. The outcome measures were Balance and cognition. The outcome tools were Berg Balance Scale, Falls Efficacy Scale, Brief Cognitive Rating Scale and Performance Oriented Mobility Assessment Scale. On comparing Pretest and Post test within Group A and Group B on Fall Efficacy Scale, Berg Balance Scale, Performance Oriented Mobility Assessment and Brief Cognitive Rating Scale shows highly significant difference in Mean values at P <0.001. Thus this study concludes that Dual Task training increases Balance and Cognition in Geriatric population